Strategies for Promoting Virtual Higher Education: General Considerations on Africa and Asia. - Kuroda, Kazuo; Shanawez, Hossain MD. (African & Asian Studies, 2003)
Education in general, and specifically higher education, plays an important role in the development process of all nations. Institutions of higher education have an important responsibility to support knowledge-driven economic growth strategies. This paper investigates the strategies of how by applying technologies on a large scale—with close attention to quality—virtual education can help higher education to find a way through the crisis of access, prohibitive cost, and lack of flexibility that we find all over the developing world. By addressing various issues related to planning, implementation, and quality with proper strategies, virtual education can provide immense opportunity to reduce the North-South knowledge gap and also to promote the development of the developing world. This paper reviews various issues related to promotion and quality control in virtual higher education and addresses possible strategies with general considerations of Africa and Asia.